Influence of Apparent Contact Area on Wear Properties of Hard-Drawn Copper Contact Wire and Iron-Based Sintered Alloy Contact Strip under Electric Current Flowing Condition - Chikara Yamashita (Japanese Society of Tribologists, 2019)
We carried out wear tests with material combination of a hard-drawn copper contact wire and an iron-based sintered alloy contact strip by changing the apparent contact area with four steps to clarify the influence of the apparent contact area on wear properties under electric current flowing condition. And we focused on a film resistance such as an oxide film and a wear particle on the contact wire surface, and considered the relationship between wear depth and wear mode transition phenomena. Based on wear properties obtained from the wear test results and microscopic observations, we clarify the phenomena that the wear mode which maximizes the wear rate of contact wire will be changed depending on the apparent contact area, and that the wear depth determined by the apparent contact area and the load are important parameters for melting of contact wire. Finally, the possibility of suppressing the maximum wear of contact wire is suggested by decreasing the film resistance of contact wire with changing the apparent contact area.